Thymocytes in Lyve1-CRE/S1pr1f/f Mice Accumulate in the Thymus due to Cell-Intrinsic Loss of Sphingosine-1-Phosphate Receptor Expression - Takeda, Akira; Hossain, Mohammad Shahadat; Rantakari, Pia; Simmons, Szandor; Sasaki, Naoko; Salmi, Marko; Jalkanen, Sirpa; Miyasaka, Masayuki (Frontiers in Immunology, 2016)
T cell emigration from the thymus is essential for immunological homeostasis. While stromal cell-produced sphingosine-1-phosphate (S1P) has been shown to promote thymocyte egress via the S1P receptor, S1PR1, the significance of S1P/S1PR1 signaling in the thymic stromal cells that surround T cells remains unclear. To address this issue, we developed conditional knockout mice (Lyve1-CRE/S1pr1f/f mice) in which S1pr1 was selectively targeted in cells expressing the lymphatic endothelial cell marker, Lyve1. In these mice, T cells were significantly reduced in secondary lymphoid tissues, and CD62L+ mature CD4 and CD8 single-positive (SP) T cells accumulated in the medulla failed to undergo thymus egress. Using a Lyve1 reporter strain in which Lyve1 lineage cells expressed tdTomato fluorescent protein, we unexpectedly found that a considerable proportion of the thymocytes were fluorescently labeled, indicating that they belonged to the Lyve1 lineage. The CD4 and CD8 SP thymocytes in Lyve1-CRE/S1pr1f/f mice exhibited an egress-competent phenotype (HSAlow, CD62Lhigh, and Qa-2high), but were CD69high and lacked S1PR1 expression. In addition, CD4 SP thymocytes from these mice were unable to migrate to the periphery after their intra-thymic injection into wild-type (WT) mice. In contrast, WT T cells could migrate to the periphery in both WT and Lyve1-CRE/S1pr1f/f thymuses. These results demonstrated that thymocyte egress is mediated by T cell-, but not stromal cell-expressed S1PR1 and caution against using the Lyve1-CRE system for selectively gene deletion in lymphatic endothelial cells.